Direct electrochemical regeneration of cathode materials from spent lithium-ion batteries: Progress, challenges, and sustainable perspectives - Pengcheng Liu; Haoran Ren; Li Xiao; Pan Tang; Like Zhang; Han Chen; Ruizhi Zhang; Tiansheng Li; Dan Xue; Sheqiang Niu (Journal of Environmental Chemical Engineering, 2026)

Burden of Clostridioides difficile infection in China, 1990–2021: an analysis based on the global burden of disease study 2021 - Wenhua Zhao; Hui Li; Maoling Hu; Tiansheng Bu (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Integrating machine learning and WGCNA to identify core candidate genes and decipher immune-related molecular networks in TcdA/TcdB-associated CDI - Wenhua Zhao; Hui Li; Maoling Hu; Tiansheng Bu (Antonie van Leeuwenhoek, 2026)

Recombinant neuropeptide Y modulates neuroendocrine signaling, inflammation, antioxidant defense, and nitrite resistance in tilapia - Ziyan Liu; Ruyue Sun; Yang Yu; Jiaqi Li; Tiansheng Zhu; Meiqing Li; Caiyun Sun; Wensheng Li (Aquaculture, 2026)

Formation mechanism and stability assessment of the Attabad landslide-dammed lake along the China-Pakistan Karakoram Highway using remote sensing technology - Yousan Li; Hongkui Yang; Lei Zheng; Wanqiang Qi; Chongyi E; Tiansheng Gao (Landslides, 2026)

Full-Length Transcriptome Analysis of the Pituitary of Pre-Matured and Artificially Matured Female Japanese Eel (Anguilla japonica) - Yu Gao; Jiangling Li; Zhenguang Feng; Mingxi Huang; Wen Li; Ruihan Xu; Ruoxue Chen; Yu Ban; Jingjie Liang; Yan Huang; Yangjie Xie; Jianchun Chen; et al. (Journal of Ocean University of China, 2026)

Establishment of a TaqMan qPCR assay for the rapid detection and quantification of Nocardia seriolae in aquaculture - Zexia Chen; Yang Yu; Tiansheng Zhu; Chaowei Song; Zijun Wang; Ziyan Liu; Ran Cai; Lei Luo; Xiangjun Miao; Wensheng Li; Caiyun Sun (Aquaculture, 2026)

Recombinant expression and identification of tilapia neuropeptide Y in Bacillus subtilis and its protective potential against ammonia stress - Ziyan Liu; Ruyue Sun; Yang Yu; Jiaqi Li; Tiansheng Zhu; Meiqing Li; Caiyun Sun; Wensheng Li (Aquaculture, 2026)

Effect of distance between active phases on the CO2 hydrogenation to aromatics over ZSM-5@S-1@InZrMg - Yihan Yin; Haibo Li; Xue Wang; Yongjie Wang; Subing Fan; Junmin Lv; Tiansheng Zhao (Fuel, 2026)

Acupuncture as a modulator of microglial polarization and pyroptosis in depression: evidence from a chronic unpredictable mild stress rat model - Xinhong Wu; Zhuoran You; Tiansheng Zhang; Jingyu Zeng; Meng Li; Simin Yan; Jianguo Li; Peng Li; Junliang Shen; Siyu Liu; Muhammad Shahzad Aslam; Jingxuan Li; et al. (Metabolic Brain Disease, 2026)

Nitrite exposure on gills of Oreochromis niloticus: structure change, immune response, and apoptosis - Chaowei Song; Tiansheng Zhu; Ran Cai; Yang Yu; Ziyan Liu; Jianing Yan; Yingying Lian; Jiaqi Li; Wensheng Li (Frontiers in Marine Science, 2025)
Nitrite is one of the most common pollutants in high-density aquaculture systems and has a potentially serious impact on the health of fish. The gill, as the organ directly in contact with the environment, performs several vital physiological functions, including gas exchange, osmotic pressure regulation, and mucosal immunity. Using a series of nitrite concentration gradients, we investigated the impact of nitrite on tilapia gills, with a focus on its immune responses. The results indicated that nitrite exposure could significantly increase the number of mucus cells and change the subtypes of chloride cells. Nitrite exposure significantly elevated serum catalase (CAT) activity and decreased superoxide dismutase (SOD) activity. After nitrite treatment, the expression of ion channel protein genes was markedly affected, with a substantial increase in Na + /Cl − cotransporter ( ncc ) expression. Inflammatory gene expression in the gill was also significantly altered. Both in vitro and in vivo experiments revealed that key genes in the IL-17 signaling pathway were considerably altered after nitrite exposure. Mitochondrial damage and apoptosis in the gill tissues were also found after nitrite exposure. In conclusion, nitrite exposure altered immune function and ion transport, especially the activation of the IL-17 signaling pathway, damage to mitochondrial structure, and apoptosis in the gill. This study enhances our understanding of the mechanisms underlying nitrite-induced damage to the gill.

International law concerning the environmental protection in Arctic: what is left behind UNCLOS and the BBNJ Agreement? - Fangling Wu; Tiansheng Li (Frontiers in Marine Science, 2025)
The Arctic region, with its unique and fragile ecosystem, faces significant challenges in environmental protection due to climate change, increasing human activities, and geopolitical tensions. This paper examines the international legal framework governing Arctic environmental protection, focusing on the roles and limitations of the United Nations Convention on the Law of the Sea (UNCLOS) and the Agreement on the Conservation and Sustainable Use of Marine Biological Diversity of Areas Beyond National Jurisdiction (BBNJ Agreement). While UNCLOS provides a foundational legal framework for ocean governance, its applicability in addressing Arctic environmental concerns should be acknowledged, as should the complementary role of the BBNJ Agreement. However, the lack of provisions specific to Arctic environmental issues creates a gap between the effectiveness of international law and the urgent need for a comprehensive legal regime tailored to the Arctic context. Furthermore, the supplementary role of the BBNJ Agreement to UNCLOS remains limited. By highlighting key challenges in the implementation of international law, including disputes over Article 234 of UNCLOS, this study underscores the urgent need for a more robust and cohesive international legal approach to ensure the sustainable future of the Arctic environment, and concludes with appropriate recommendations.

Enhancing spectral estimation accuracy of soil organic carbon by using geographic region and clay content as covariates - Wenxu Zhang; Haijiang Wang; Cuncang Jiang; Jing Cui; Jianghui Song; Xiaoyan Shi; Xiang Xing; Jingang Wang; Tiansheng Li; Weidi Li (Journal of Environmental Management, 2025)

Calycosin alleviates ovariectomy-induced osteoporosis by promoting BMSCs autophagy via the PI3K/Akt/mTOR pathway - Shouyu Xiang; Yinji Luo; Wei Liu; Cheng Tang; Tianyu Zhu; Lai Tian; Tiansheng Zheng; Long Ling; Mingyang Jia; Xing Li; Yanming Cao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Study on the separation of nitric acid and acetic acid using multi-stage electrodialysis - Xiao Ge; Baole Li; Xiang Meng; Tiansheng He; Tianchi Li; Qi Yang; Zheng Wei; Taihong Yan; Zhongwei Yuan (Desalination, 2025)

Air flow field Testing, simulation and Optimization of CO2 air-source heat pump outdoor unit arrays - Li Xiaoyu; Shi Lin; Ma Li; Xu We; Wang Tiansheng; Zheng Siyu; Tian Ran; Yuan Jing; Cui Yujia (Energy and Buildings, 2025)

Improving para-xylene and low olefins by coupling aromatization of methanol with CO - Haibo Li; Yihan Yin; Yongjie Wang; Subing Fan; Junmin Lv; Tiansheng Zhao (Chemical Engineering Journal, 2025)

Effect of temperature fluctuations on large yellow croaker fillets (Larimichthys crocea) in cold chain logistics: A microbiological and metabolomic analysis - Bohan Chen; Tiansheng Xu; Qi Yan; Baris Karsli; Dapeng Li; Jing Xie (Journal of Food Engineering, 2025)

Mechanism of cadmium (Cd) enrichment in the soil of karst areas with high geochemical background in Southwest China - Bo Li; Kun Lin; Xu Liu; Xudong Ma; Xuezhen Li; Zhiliang Wu; Cheng Li; Tao Yu; Tiansheng Wu; Zhongfang Yang (Chemical Geology, 2025)

Institutional consequences and mechanism adjustments to China's international ship registration policy—Taking the Red Sea crisis as an Example - Linhan Xiang; Tiansheng Li (Marine Policy, 2025)

In situ construction of ion/electron conductive components via lithiation strategy enhancing cycling capability and initial Coulombic efficiency of Si anode - Jingfeng Cao; Xiang Yan; Dan Li; Liuyi Hu; Tiansheng Chen; Weiwei Gao; Wenlong Song; Xinhui Xia; Yang Xia; Wenkui Zhang; Hui Huang (Chemical Engineering Journal, 2025)

Large-scale structural covariance networks changes relate to executive function deficit in betel quid-dependent chewers - Yihao Guo; Tao Liu; Xiaoling Xu; Tiansheng Li; Xiaoli Xiong; Huijuan Chen; Weiyuan Huang; Xianchang Zhang; Feng Chen (Brain Imaging and Behavior, 2024)

Improved mapping of heavy metals in agricultural soils using machine learning augmented with spatial regionalization indices - Xudong Ma; Dong-Xing Guan; Chaosheng Zhang; Tao Yu; Cheng Li; Zhiliang Wu; Bo Li; Wenda Geng; Tiansheng Wu; Zhongfang Yang (Journal of Hazardous Materials, 2024)

In situ synthesis of Rh@NaX catalyst for 1-hexene hydroformylation - Gongcheng Sun; Wan Chen; Yaoying Li; Subing Fan; Junmin Lv; Tiansheng Zhao (Fuel, 2024)

Specific spoilage bacteria in cold chain logistics: A study on ATP-related compounds degradation in large yellow croaker (Larimichthys crocea) - Bohan Chen; Tiansheng Xu; Qi Yan; Dapeng Li; Jing Xie (Food Bioscience, 2024)

Photo-production of excited triplet-state of dissolved organic matters in inland freshwater and coastal seawater - Zhongyu Guo; Tingting Wang; Hidetaka Ichiyanagi; Mohamed Ateia; Guo Chen; Jieqiong Wang; Manabu Fujii; Kaichii En; Tiansheng Li; Rumi Sohrin; Chihiro Yoshimura (Water Research, 2024)

Combination of feature selection and geographical stratification increases the soil total nitrogen estimation accuracy based on vis-NIR and pXRF spectral fusion - Jianghui Song; Xiaoyan Shi; Haijiang Wang; Xin Lv; Wenxu Zhang; Jingang Wang; Tiansheng Li; Weidi Li (Computers and Electronics in Agriculture, 2024)

Dual strategies of interface engineering and core–shell structure improve potassium storage performance - Yifei Xu; Yuhao Li; Tiansheng Wang; Qingshan Liu; Xinrui Fang; Xueting Ding; Zhengyuan Chen; Cunliang Zhang; Haitao Niu; Hua Zhou; Hongsen Li (Chemical Engineering Journal, 2024)

Spatially varying relationships of soil Se concentration and rice Se concentration in Guangxi, China: A geographically weighted regression approach - Bo Li; Xu Liu; Chaosheng Zhang; Tao Yu; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Lei Wang; Kun Lin; Xudong Ma; Xuezhen Li; Husheng Zhang; et al. (Chemosphere, 2023)

Stability Analysis and Deformation Control of Tunnel with Extremely Weak Surrounding Rocks Caused by Strike-Slip Fault Activity - Ziquan Chen; Qixiang Yan; Zihan Zhou; Chuan He; Tiansheng Li; Yeming Bao (Rock Mechanics and Rock Engineering, 2023)

Comparative study of compressive behavior of confined NSC and UHPC/UHPFRC cylinders externally wrapped with CFRP jacket - Weiwen Li; Yao Lu; Peng Wang; Yuanhui Jiang; Le Wang; Tiansheng Shi; Kailun Zheng (Engineering Structures, 2023)

Photothermal-assisted for ultrafast response acetone sensing with ZIF-90/GO coated microfiber long period gratings - Yan Huang; Wenfu Lin; Ziruo Zhang; Zhenru Li; Tiansheng Huang; Jie Li; Li-Peng Sun; Bai-Ou Guan (Chemical Engineering Journal, 2023)

Insights into electrogenerated intermediates and rapid screening of electrochemical reactions by surface-modified carbon fiber paper redox spray ionization mass spectrometry - Jiahui Bai; Mingmai Bao; Shanshan Wang; Tianlun Wen; Yuling Li; Jing Zhang; Tiansheng Mei; Yinlong Guo (Analytica Chimica Acta, 2023)

Sodium selenite inhibits proliferation of lung cancer cells by inhibiting NF-κB nuclear translocation and down-regulating PDK1 expression which is a key enzyme in energy metabolism expression - Xiao Xu; Yaqin Hou; Shumeng Lin; Kai Wang; Yanbei Ren; Tiansheng Zheng; Xi Zhang; Ming Li; Lihong Fan (Journal of Trace Elements in Medicine and Biology, 2023)

Identification of the spatial patterns and controlling factors of Se in soil and rice in Guangxi through hot spot analysis - Xu Liu; Chaosheng Zhang; Tao Yu; Wenbing Ji; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Bo Li; Lei Wang; Yuxiang Shao; Kun Lin; Xudong Ma; et al. (Environmental Geochemistry and Health, 2023)

Diversity of Wolbachia infection and its influence on mitochondrial DNA variation in the diamondback moth, Plutella xylostella - Xiangyu Zhu; Tiansheng Liu; Ao He; Ling Zhang; Jinyang Li; Tianpu Li; Xin Miao; Minsheng You; Shijun You (Molecular Phylogenetics and Evolution, 2023)

Identification of high ecological risk areas with naturally high background value of soil Cd related to carbonate rocks - Xu Liu; Tao Yu; Chaosheng Zhang; Cheng Li; Bo Li; Zhongfang Yang; Qiong Yang; Yiren Duan; Wenbing Ji; Tiansheng Wu; Lei Wang (Environmental Geochemistry and Health, 2023)

Influence of faults on the geo-stress field distribution and damage evolution mechanism of fracture zones - Ziquan Chen; Zihan Zhou; Chuan He; Changwei Jiang; Bo Wang; Tiansheng Li (Bulletin of Engineering Geology and the Environment, 2023)

Higher BTX yield in coaromatization of n-hexane and methanol over [Zn,Ga]/HZSM-5 catalyst - Haibo Li; Bing Zhu; Xue Wang; Junmin Lv; Subing Fan; Tiansheng Zhao (Fuel, 2023)

Study on the Applicability of Various In-situ Stress Inversion Methods and Their Application on Sinistral Strike-Slip Faults - Zihan Zhou; Ziquan Chen; Bo Wang; Changwei Jiang; Tiansheng Li; Wei Meng (Rock Mechanics and Rock Engineering, 2023)

Facile construction of Z-scheme AgCl/Bi3TaO7 photocatalysts for effective removal of tetracycline under visible-light irradiation - Xiaoxin Guo; Jun Liu; Dan Li; Hongjun Cheng; Kankan Liu; Xiaoqing Liu; Tiansheng Liu (Environmental Science and Pollution Research, 2023)

Qualitative and quantitative analysis of refined F–T wax on GC–MS and GC - Songpeng Cheng; Liangcheng An; Zhenling Li; Suli Liu; Junmin Lv; Subing Fan; Tiansheng Zhao (Fuel, 2023)

Auxiliary thermodynamic analysis support capturing the differences in nanostructured FeVO4·nH2O electrodes between lithium and sodium ions storage mechanism - Linyi Zhao; Tiansheng Wang; Fei Li; Yongshuai Liu; Fengkai Zuo; Li Yang; Yifei Xu; Cunliang Zhang; Huaizhi Wang; Jie Liu; Xiaotong Dong; Shikai Zhu; et al. (Chemical Engineering Journal, 2023)

Interface regulation of Mg anode and redox couple conversion in cathode by copper for high-performance Mg-S battery - Rupeng Zhang; Can Cui; Rang Xiao; Ruinan Li; Tiansheng Mu; Hua Huo; Yulin Ma; Geping Yin; Pengjian Zuo (Chemical Engineering Journal, 2023)

The association between ethylene oxide exposure and asthma risk: a population-based study - Ziye Li; Pingfan Shi; Zhibo Chen; Wenjia Zhang; Shumeng Lin; Tiansheng Zheng; Ming Li; Lihong Fan (Environmental Science and Pollution Research, 2022)

Novel EST-SSRs for an important quarantine pest Liriomyza sativae (Diptera: Agromyzidae) and their cross-species transferability - Tiansheng Liu; Xue Zhan; Jinyu Li; Fushi Ke; Xiangyu Zhu; Yanting Chen; Weiyi He; Shijun You (Applied Entomology and Zoology, 2022)

Synergistic use of spectral features of leaf nitrogen and physiological indices improves the estimation accuracy of nitrogen concentration in rapeseed - Tian Tian; Jingang Wang; Haijiang Wang; Jing Cui; Xiaoyan Shi; Jianghui Song; Tiansheng Li; Weidi Li; Mingtao Zhong (International Journal of Remote Sensing, 2022)

The Fvclp1 gene regulates mycelial growth and fruiting body development in edible mushroom Flammulina velutipes - Xiaomeng Lyu; Siyuan Jiang; Li Wang; Tiansheng Chou; Qingji Wang; Li Meng; Irum Mukhtar; Baogui Xie; Wei Wang (Archives of Microbiology, 2021)

Monitoring of leaf nitrogen content of winter wheat using multi-angle hyperspectral data - Tiansheng Li; Zhen Zhu; Jing Cui; Jianhua Chen; Xiaoyan Shi; Xu Zhao; Menghao Jiang; Yutong Zhang; Weiju Wang; Haijiang Wang (International Journal of Remote Sensing, 2021)

Characterization and expression pattern analysis of pheromone receptor-like genes in Winter Mushroom Flammulina filiformis - Li Meng; Tiansheng Chou; Siyuan Jiang; Li Wang; Mengjuan Zhu; Irum Mukhtar; Baogui Xie; Wei Wang (Archives of Microbiology, 2020)

Optimal design of groundwater pollution monitoring network based on the SVR surrogate model under uncertainty - Yue Fan; Wenxi Lu; Tiansheng Miao; Yongkai An; Jiuhui Li; Jiannan Luo (Environmental Science and Pollution Research, 2020)

Optimum Design of a Seawater Intrusion Monitoring Scheme Based on the Image Quality Assessment Method - Yue Fan; Wenxi Lu; Tiansheng Miao; Jiuhui Li; Jin Lin (Water Resources Management, 2020)

Multiobjective optimization of the groundwater exploitation layout in coastal areas based on multiple surrogate models - Yue Fan; Wenxi Lu; Tiansheng Miao; Jiuhui Li; Jin Lin (Environmental Science and Pollution Research, 2020)

Effect of cytochrome P450 2C19 polymorphisms on the clinical outcomes of voriconazole: a systematic review and meta-analysis - Xiaofei Li; Caiyuan Yu; Tiansheng Wang; Ken Chen; Suodi Zhai; Huilin Tang (European Journal of Clinical Pharmacology, 2016)

Fracture initiates systemic inflammatory response syndrome through recruiting polymorphonuclear leucocytes - Haipeng Li; Jia Liu; Jianhua Yao; Jianfeng Zhong; Lei Guo; Tiansheng Sun (Immunologic Research, 2016)

Integrating Genome-Wide Association Study and Brain Expression Data Highlights Cell Adhesion Molecules and Purine Metabolism in Alzheimer’s Disease - Zimin Xiang; Meiling Xu; Mingzhi Liao; Yongshuai Jiang; Qinghua Jiang; Rennan Feng; Liangcai Zhang; Guoda Ma; Guangyu Wang; Zugen Chen; Bin Zhao; Tiansheng Sun; et al. (Molecular Neurobiology, 2015)